Language History Contents in the Curriculum Concept of Teaching Croatian Language - Vignjevic, Jelena (European Scientific Journal, ESJ, 2017)
The paper analyses the scope of educational content pertaining to the history of language in the curriculum of the subject Croatian Language. The context of this examination is the curricular reform in the Republic of Croatia, which is conceived as a turning point of Croatian education away from the traditional didactic concept toward the curriculum concept. The issue of curriculum contents’ scope as part of the curriculum teaching concept is concretised by comparing the representation of contents pertaining to the history of Croatian language in the proposal of the National Curriculum Framework with the current Plan and Programme for Primary and Secondary Schools. The comparison demonstrates that in the proposal of the National Curriculum Framework educational content in the area of the history of Croatian language has been considerably reduced in relation to the current plan and programme. The same document, National Curriculum Framework, cites identity building as one of the values of education, emphasizing the construction of a national identity and, in particular, the need to preserve and develop the Croatian language. The question arises of how to attain the stated value of education in the absence of transferring the contents of Croatian linguistic history to pupils. Undoubtedly, students need both â€“ knowledge of language content and communicative competence in the mother tongue. It is therefore necessary to harmonise the relationship between educational content and the acquisition of communication skills in teaching practice and in school documents.